2022
DOI: 10.3390/life12122052
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Non-Alcoholic Fatty Liver Disease in Infections

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disease, affecting one third of the Western population. The hallmark of the disease is excessive storage of fat in the liver. Most commonly, it is caused by metabolic syndrome (or one of its components). Even though the development of NAFLD has multiple effects on the human organism resulting in systemic chronic low-grade inflammation, this review is focused on NAFLD as a risk factor for the onset, progression, and outcomes of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Importantly, NAFLD is now considered a multisystemic disease associated with a variety of extrahepatic complications, such as an increased cardiovascular risk, extrahepatic cancer or chronic kidney disease [ 4 ]. In the pre-COVID-19 era, the role of NAFLD in infectious diseases was largely overlooked [ 5 , 6 ]. However, in an attempt to better understand COVID-19 and find potential therapeutic options, the pandemic has yielded scientific research that has shed new light on the intertwined relationship between NAFLD and infection [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, NAFLD is now considered a multisystemic disease associated with a variety of extrahepatic complications, such as an increased cardiovascular risk, extrahepatic cancer or chronic kidney disease [ 4 ]. In the pre-COVID-19 era, the role of NAFLD in infectious diseases was largely overlooked [ 5 , 6 ]. However, in an attempt to better understand COVID-19 and find potential therapeutic options, the pandemic has yielded scientific research that has shed new light on the intertwined relationship between NAFLD and infection [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that the detection rate of Porphyromonas gingivalis, a periodontal pathogen, was significantly higher in patients with NAFLD compared to the control group. 31 NAFLD can present with various extrahepatic manifestations, including complications such as CP. 32 Although the results of the aforementioned studies suggest an association between CP and NAFLD, they do not establish a causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…As a common oral infectious disease, CP is related to the occurrence and progression of NAFLD. A recent study showed that the detection rate of Porphyromonas gingivalis , a periodontal pathogen, was significantly higher in patients with NAFLD compared to the control group 31 . NAFLD can present with various extrahepatic manifestations, including complications such as CP 32 .…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 24 Emerging evidence suggests that several viral and bacterial infections may impact the pathobiology of MAFLD, and those infections may take a more aggressive course in patients with MAFLD. 25 …”
mentioning
confidence: 99%
“…22,24 Emerging evidence suggests that several viral and bacterial infections may impact the pathobiology of MAFLD, and those infections may take a more aggressive course in patients with MAFLD. 25 There is a bidirectional relationship between the gut and liver, known as the gut-liver axis, wherein the gut microbiota and gut-derived metabolic byproducts directly affect the liver. 26 On the other hand, liver-derived bile acids and antibodies directly affect the gut microbiota.…”
mentioning
confidence: 99%